The Analysis of a Choir as a Discourse Community (Bridging Cultures, 2019)
This paper aims at delving into the topic of discourse analysis and discourse communities byexamining two discourse samples from a choir. In the first place, a music score is analyzed interms of written discourse, and the similarities between language and music are examined.Secondly, the paper explores the topic of non-verbal communication. The gestures with which the director of the choir communicates are analyzed with the objective of appreciating how important non-verbal communication is for a choir. Finally, an assessment is made as to whether this discourse community is able to communicate in a meaningful and effective way.
Keywords: Discourse Analysis; Discourse Community; Choir; Music Score; Written Discourse; Non-Verbal Communication